A history of water engineering and management in Yemen : material remains and textual foundations - Hehmeyer, Ingrid (Leiden ; Boston : Brill, 2019)
"In A History of Water Engineering and Management in Yemen, Ingrid Hehmeyer describes the three-way relationship between water, land, and humans from ancient to medieval and premodern times. As illustrated in case studies from four sites, individual ecosystems necessitated different engineering and management approaches in order to make good use of the scarce water resources for both irrigated agriculture and domestic consumption. Material remains and written sources provide the evidence for a comprehensive examination of continuity and change; technical and managerial struggles, failures, and successes; the question of technology transfer; the impact of the religion of Islam on water use and allocation; and people's reactions in times of severe crisis."--Back cover
Front Matter -- Copyright page -- Acknowledgements -- A Note on Transliteration -- Figures and Tables -- Photo Credits and Permissions for Reproduction -- Introduction -- Irrigated Agriculture in Ancient South Arabia: The Oasis of Mārib -- Introduction to Part I -- Agricultural Practices in the Controlled Irrigation Network of Ancient Mārib -- The City of Zabīd (Founded 820 CE) and its Agricultural Hinterland before the First Ottoman Conquest in 1539 -- Introduction to Part II -- Sayl Irrigation in the Wādī Zabīd -- The Importance of the Agricultural Hinterland to Pre-Ottoman Zabīd -- Engineered Water Systems in the Wādī Zabīd -- Water and Waste in the City of Zabīd -- Water and Settlement on the Coastal Plain of Southern Yemen: The Example of Ghayl Bā Wazīr -- Introduction to Part III -- Tapping Underground Water: The Maʻyān System of Ghayl Bā Wazīr -- Water-Storage Systems in the Western Highlands of Yemen: The Cisterns of al-Jabīn -- Introduction to Part IV -- The Study and Restoration of Birkat ʻĀṭif, a Public Cistern in al-Jabīn -- Water and Religious Magic -- Introduction to Part V -- Water and Religious Magic -- Concluding Remarks -- Back Matter -- Glossary -- Works Cited -- Index.
Includes bibliographical references and index
In English; some text in Arabic.
Print version record
eBooks on EBSCOhost
Keywords: Water-supply engineering -- Yemen (Republic) -- History; Water-supply -- Yemen (Republic) -- History; Eau -- Approvisionnement -- Technique -- Yémen -- Histoire; Eau -- Approvisionnement -- Yémen -- Histoire; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Water-supply; Water-supply engineering; Yemen (Republic); History